HUBUNGAN EFIKASI DIRI DENGAN COPING STRESS PADA MAHASISWA ANGKATAN 2012 FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Rizky, Elsavina; ", Zulharman (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Student in education life will face many obstacles where good self adapted and readiness is needed. Coping stress is a good principal for students to face their problems. Coping stress can be influenced by internal factors and external factors, one of internal factor is self efficacy. This research conducted to discover correlation between self efficacy and coping stress on medical students of Riau University on year 2012. This is an analytic correlation study with cross sectional approachment. Subjects were medical students of Riau University on year 2012, where 107 students were obtained as samples with total sampling method. Instruments used in this research were Bandura’s based theory self efficacy questionnaire and Lazarus and Folkman’s based theory coping stress questionnaire. The result showed that about 68 students (63,6 %) used to used problem focused coping, 39 students (36,4 %) applicated emotional focused coping and about 60 students (24 %) have high self efficacy, 47 students (43,9 %) with average self efficacy, and none student with low self efficacy could be found. Statistic test used to discover correlation between self efficacy and coping stress was Lambda statistic test. The result showed that there was positive, significant, and poor correlation between self efficacy and coping stress (r= 0,278; p= 0,000), which led to a conclusion that correlation between self efficacy and coping stress on medical students of Riau University on year 2012 could be found.Keywords: self efficacy, coping stressPENDAHULUANMahasiswa sebagai salah seorang pelajar dituntut untuk dapat mengembangkan diri dengan maksimal dalam berbagai masalah. Masalah-masalah yang umumnya dihadapi mahasiswa adalah masalah akademik, masalah ekonomi, masalah keluarga, dan kesehatan. Semua masalah tersebut merupakan tuntutan yang memerlukan kesiapan maupun penyesuaian diri yang baik bagi mahasiswa itu sendiri, sehingga